CaMn(4)O(2) model of the biological Oxygen Evolving Complex: Synthesis by cluster expansion on low symmetry ligand - Lee, Heui Beom (Chem Commun (Camb), 2017)
Using a new multinucleating ligand featuring two dipyridylalkoxide and a carboxylate moiety, low symmetry tetranuclear complexes 1-M (M = Mn, Fe, and Co) have been synthesized. Complex 1-Mn was used as precursor for the synthesis of a pentanuclear CaMn(4)O(2) cluster (3) with the same metal stoichiometry as the biological OEC.